PREDICTORS THAT LEADS TO SOCIO ECONOMIC SUCCESS OF LOCAL COMMUNITIES - Haudi, .; Aseh, Khairi; Kenny, Kamal; Pathmathan, P. Ravindran (Archives of Business Research, 2020)
In Malaysia, the infusion of private and public sectors has attributed to the nation’s socio-economic development as strengthen by the need to address the demands and challenges of the local community. These efforts will more likely provide several important ideas that would suffice related and relevant literatures, which will be used to develop a better socio-economic growth in Malaysia. In an economic sense, development entails the transformation of simple subsistence economies into complex monetary economies. In the process, an increase in the proportion of products that are sold or exchanged and a decline in the proportion of consumption may take place concurrently. The purpose of this study is to examine the socio-economic demands and gaps of the local population and to suggest assistance and interventions required. The overall results of this study reveal the challenges faced at the community level in the District of Kuala Lipis in the context of social and economy. This study was carried out via a structured survey throughout the district involving 300 respondents and also complemented with a face-to-face interview carried out with key stakeholders. The study findings were also supported with secondary data compilation of journals, articles and speeches.